An ancestral MADS-box gene duplication occurred before the divergence of plants and animals - Alvarez-Buylla, Elena R. (The National Academy of Sciences, 2000)
Changes in genes encoding transcriptional regulators can alter development and are important components of the molecular mechanisms of morphological evolution. MADS-box genes encode transcriptional regulators of diverse and important biological functions. In plants, MADS-box genes regulate flower, fruit, leaf, and root development. Recent sequencing efforts in Arabidopsis have allowed a nearly complete sampling of the MADS-box gene family from a single plant, something that was lacking in previous phylogenetic studies. To test the long-suspected parallel between the evolution of the MADS-box gene family and the evolution of plant form, a polarized gene phylogeny is necessary. Here we suggest that a gene duplication ancestral to the divergence of plants and animals gave rise to two main lineages of MADS-box genes: TypeI and TypeII. We locate the root of the eukaryotic MADS-box gene family between these two lineages. A novel monophyletic group of plant MADS domains (AGL34 like) seems to be more closely related to previously identified animal SRF-like MADS domains to form TypeI lineage. Most other plant sequences form a clear monophyletic group with animal MEF2-like domains to form TypeII lineage. Only plant TypeII members have a K domain that is downstream of the MADS domain in most plant members previously identified. This suggests that the K domain evolved after the duplication that gave rise to the two lineages. Finally, a group of intermediate plant sequences could be the result of recombination events. These analyses may guide the search for MADS-box sequences in basal eukaryotes and the phylogenetic placement of new genes from other plant species.